"More than skin deep": stress neurobiology and mental health consequences of racial discrimination. (January 2015) - Berger, Maximus; Sarnyai, Zoltán
Abstract Ethnic minority groups across the world face a complex set of adverse social and psychological challenges linked to their minority status, often involving racial discrimination. Racial discrimination is increasingly recognized as an important contributing factor to health disparities among non-dominant ethnic minorities. A growing body of literature has recognized these health disparities and has investigated the relationship between racial discrimination and poor health outcomes. Chronically elevated cortisol levels and a dysregulated hypothalamic–pituitary–adrenal (HPA) axis appear to mediate effects of racial discrimination on allostatic load and disease. Racial discrimination seems to converge on the anterior cingulate cortex (ACC) and may impair the function of the prefrontal cortex (PFC), hence showing substantial similarities to chronic social stress. This review provides a summary of recent literature on hormonal and neural effects of racial discrimination and a synthesis of potential neurobiological pathways by which discrimination affects mental health.